Labranza mecanizada en la productividad del cultivo de maíz h. Trueno - Mendoza Alcívar, Magno Rafael (2015)
The present research aimed to validate tillage systems and their impact on the physical, chemical, and biological properties of the soil, and their influence on the productivity of H. Trueno corn crop. This study was carried out in “El Bejucal”, parish of Canuto in the canton of Chone–Manabí from January to May 2013; the treatments over study were as follow: conventional tillage, minimum tillage, and zero tillage (control). For the implementation in field the systematic design Zade with a control treatment was carried out over four replicates. Significance was determined using a T-test at P < 0.05; the results on soil physical characteristics showed no statistical differences among treatments, keeping the same preplant values, in terms of chemical characteristics conventional tillage showed the highest values, regarding the biological component, it was not affected by the different tillage systems. The vegetative crop variables showed no significant statistical differences among treatments; however, in the productive variables, there were statistical significant differences for both conventional and minimum tillage which showed superior performance compared to the control.